2018
DOI: 10.1007/s00406-018-0897-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum lipid levels, osteoprotegerin and depressive symptomatology in psychotic disorders

Abstract: Although the relationship between positive and negative symptoms of psychosis and dyslipidemia has been thoroughly investigated in recent studies, the potential link between depression and lipid status is still under-investigated. We here examined the association between lipid levels and depressive symptomatology in patients with psychotic disorders, in addition to their possible inflammatory associations. Participants (n = 652) with the following distribution: schizophrenia, schizophreniform and schizoaffecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 53 publications
2
16
1
Order By: Relevance
“…The methodology used for drawing, processing and storage of blood samples have been described previously (24). Some of these biological markers have been reported previously by us in relation to other outcome measures (25)(26)(27)(28)(29)(30).…”
Section: Blood Samplesmentioning
confidence: 99%
“…The methodology used for drawing, processing and storage of blood samples have been described previously (24). Some of these biological markers have been reported previously by us in relation to other outcome measures (25)(26)(27)(28)(29)(30).…”
Section: Blood Samplesmentioning
confidence: 99%
“…Depression may be associated with lipid profiles and inflammatory cytokines [28, 29]. In this study, after categorization by depression status, a significant association was found between depression status and waist circumference, fat percentage, diastolic blood pressure, LDL, TG, and FBS.…”
Section: Discussionmentioning
confidence: 55%
“…In addition, accumulating evidence suggests that various psychiatric disorders including depression can be affected by the altered lipids levels (TC, TG, LDL, and HDL). 18,19 Lipids are found to be involved in the neuronal function of the brain, influencing emotional behaviours and mental disorders. 20 Depression and elevated total cholesterol are identified as an independent and potent risk factor for cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%